Reconstructing Zakat on Cryptocurrency: A Maqāṣid al-Sharī‘ah-Based Comparative Analysis of Indonesia, Malaysia, and Egypt - Muhammad Nur Karim Al Ismariy; Ridho Saadillah Ahmad; Aan Taufiqurrohman; Mohammad Tohari; Jean Claude Geofrey Mahoro (Walisongo Journal of Sharia Economic Law, 2026)
The rapid development of the global digital economy has introduced new forms of wealth, particularly cryptocurrency, which challenge traditional constructs of Islamic economic law, including zakat. This study aims to analyze the legal position of zakat on cryptocurrency in Indonesia within the context of global digital economic trends and to formulate a maqāṣid al-sharīʿah-based reconstruction of zakat applicable to digital assets. A normative-comparative research methodology was employed, combining doctrinal analysis of Islamic legal texts, national regulations, fatwas from Indonesia, Malaysia, and Egypt, as well as scholarly literature indexed in Scopus. The study systematically examines regulatory gaps, jurisprudential interpretations, and institutional practices concerning cryptocurrency zakat. Findings indicate that while cryptocurrency conceptually qualifies as zakatable wealth if conditions of ownership, nisab, haul, and lawful source are fulfilled, Indonesia currently lacks explicit normative provisions, resulting in legal vacuum. Malaysia demonstrates an adaptive and operational approach, allowing zakat payment through Shariah-compliant cryptocurrency under state fatwas, whereas Egypt maintains a restrictive stance, though acknowledging zakat obligations if criteria are met. The study concludes that a maqāṣid al-sharīʿah-based reconstruction integrating fiqh principles, national regulation, and digital mechanisms is essential for strengthening Indonesia’s national zakat system. Recommendations include revising national zakat law, establishing technical guidelines for digital asset valuation and reporting, and implementing blockchain-based platforms to ensure transparency, accountability, and effective wealth redistribution.